Economic Dispatch Pada Pembangkit Listrik Tenaga Diesel Gas (PLTDG) Menggunakan Fuzzy Logic Controller (FLC) - Winasatria, I Made Teguh; Mataram, I Made; Manuaba, Ida Bagus Gde (Majalah Ilmiah Teknologi Elektro, 2019)
In fulfilling current electrical energy needs, a power plant unit is operated using various fuels. The biggest cost of the total operating costs of the plant is the cost of using the generator unit fuel which is around 60%, therefore a solution is needed to be able to minimize the costs of using generator fuel in operating the generating unit. Economic Dispatch is a way to overcome the economic operating problem of a power plant by dividing the load on each operating unit so that the minimum generation cost is obtained. The solution to the Economic Dispatch problem can be done using the Fuzzy Logic Controller (FLC) method because the FLC method can make very complex decisions and in its application does not require mathematical models that are too difficult to solve, so the FLC method is expected to minimize the cost of generating electricity. The results of calculating the Economic Dispatch using the FLC method result in a lower total production cost compared to the total total production costs of the System and the Lamda Iteration method for 24 hours on September 30, 2017.